A successful case of percutaneous fistula closure in a patient with high output heart failure and extracardiac arteriovenous fistula. Issue 4 (April 2019) - Kato, Yukiko; Nakayama, Takafumi; Yamamoto, Junki; Muto, Keisuke; Kitada, Shuichi; Suzuki, Kazushi; Shimohira, Masashi; Kamiya, Shinji; Suda, Hisao; Ohte, Nobuyuki
Abstract: Intra-cardiac shunt diseases may cause chronic ventricular volume overload, but extra-cardiac fistula could also cause high-output heart failure (HF). A patient presented with high-output HF and significant extra-cardiac shunt flow. Although the size and shape of the patient's left ventricle suggested dilated cardiomyopathy, considerable origins were not identified except for a high-flow fistula between the right subclavian artery and right internal jugular vein. Right heart catheter examination revealed inappropriately high cardiac output. Left-to-right shunt ratio was calculated at 40.3% from an oximetry run, under the assumption that the left anonymous vein which was not contaminated with any shunt flow could be substituted for venous return from the upper body. We could determine the indication of fistula closure according to the estimated high left-to-right shunt ratio, reducing cardiac output by 42.7% which was similar to the pre-estimated left-to-right shunt ratio. Two months later, the patient's serum B-type natriuretic peptide level and left ventricular end-diastolic and end-systolic diameters were decreased. The proposed method to estimate the left-to-right shunt ratio was useful in determining the indication for fistula closure in a patient with HF and a significant shunt fistula. <Learning objective: A significant extracardiac left-to-right shunt more than 30–35% could cause heart failure with left ventricular dilatation similar to dilated cardiomyopathy. One can decide fistula closure with the finding of left-to-right shunt ratio calculated using a transcatheter oximetry run. It is mandatory that the venous oxygen saturation at the upper stream of fistula is determined precisely without the contamination of arterial blood. In this case, the oxygen saturation at the left anonymous vein substituted for it.>